Biomass-derived porous carbon-based nanostructures for microwave absorption - Zhao, Huanqin (2019)
Currently, electromagnetic (EM) pollution poses severe complication toward the operation of electronic devices and biological systems. To this end, it is pertinent to develop novel microwave absorbers through compositional and structural design. Porous carbon (PC) materials demonstrate great potential in EM wave absorption due to their ultralow density, large surface area, and excellent dielectric loss ability. However, the large-scale production of PC materials through low-cost and simple synthetic route is a challenge. Deriving PC materials through biomass sources is a sustainable, ubiquitous, and low-cost method, which comes with many desired features, such as hierarchical texture, periodic pattern, and some unique nanoarchitecture. Using the bio-inspired microstructure to manufacture PC materials in mild condition is desirable. In this review, we summarize the EM wave absorption application of biomass-derived PC materials from optimizing structure and designing composition. The corresponding synthetic mechanisms and development prospects are discussed as well. The perspective in this field is given at the end of the article.